Hydroxyurea-Induced Accumulation of Short Fragments During Polyoma DNA Replication I. Characterization of Fragments - Magnusson, Göran (1973)
Hydroxyurea treatment of 3T6 mouse fibroblast cells infected with polyoma virus resulted within 15 min in more than a 20-fold reduction of the rate of both viral and cellular DNA synthesis. After the initial rapid inhibition, the rate of DNA synthesis remained essentially constant for at least 2 h. In the inhibited cells viral DNA accumulated as short chains with a sedimentation coefficient of about 4S (hydroxyurea fragments). A variable proportion of these fragments was released from the template strands when the viral DNA was extracted by the Hirt procedure. Reannealing experiments demonstrated that hydroxyurea fragments were polyoma-specific and probably synthesized on both parental strands at the replication forks.